Does the Ischemic Core Really Matter? An Updated Systematic Review and Meta‐Analysis of Large Core Trials After TESLA, TENSION, and LASTE - AlMajali, Mohammad; Dibas, Mahmoud; Ghannam, Malik; Galecio‐Castillo, Milagros; Qudah, Abdullah Al; Khasiyev, Farid; Vivanco‐Suarez, Juan; Rodriguez‐Calienes, Aaron; Farooqui, Mudassir; Shogren, Sophie L.; AlMajali, Fawaz; Yoo, Albert; et al. (Stroke: vascular and interventional neurology, 2024)
BackgroundThe available evidence supporting the use of endovascular thrombectomy (EVT) in acute ischemic stroke patients with large core has increased with the recent release of the Thrombectomy for Emergent Salvage of Large Anterior Circulation Ischemic Stroke (TESLA), Efficacy and Safety of Thrombectomy In Stroke with Extended Lesion and Extended Time Window (TENSION), and Large Stroke Therapy Evaluation (LASTE) trials, providing critical information on additional subgroups not included in initial trials. We aimed to study the efficacy and safety of EVT in patients with acute ischemic stroke with large core and stratify by several subgroups including core infarct at presentation, using a comprehensive meta‐analysis of aggregate data.MethodsWe executed a systematic search to identify randomized controlled trials that compared EVT to medical management (MM) for the treatment of patients with acute ischemic stroke with large core, defined as Alberta Stroke Program Early CT [Computed Tomography] Score ≤5 on noncontrast CT and/or estimated ischemic core ≥50 mL on CT‐perfusion/MR diffusion. The primary outcome was the shift analysis in the 90‐day modified Rankin scale (mRS) score. Secondary outcomes included functional independence (mRS score 0–2), independent ambulation (mRS score 0–3), 90‐day mortality, and symptomatic intracranial hemorrhage. Pooled odds ratios were calculated for shift mRS score through the random‐effects meta‐analyses, and risk ratios (RRs) were used for the other outcomes, comparing EVT with MM alone.ResultsOut of 3402 titles and abstracts screened, 6 randomized controlled trials with 1886 patients were included. The EVT group had a higher shift toward a lower mRS than MM alone (odds ratio [OR], 1.49 [95% CI, 1.24–1.79]). Furthermore, the use of EVT was associated with higher rates of functional independence (19.5% versus 7.5%, RR, 2.49 [95% CI, 1.92–3.24]), independent ambulation (36.5% versus 19.9%, RR, 1.91 [95% CI, 1.51–2.43]), and symptomatic intracranial hemorrhage (5.5% versus 3.2%, RR, 1.73 [95% CI, 1.01–2.95]) compared with MM. There was no difference between the 2 groups regarding mortality (31.5% versus 36.8%, RR, 0.86 [95% CI, 0.72–1.02]). Importantly, EVT was consistently associated with a shift toward a lower mRS score in both Alberta Stroke Program Early CT Score 3–5 (OR, 1.60 [95% CI, 1.10–2.32]) and Alberta Stroke Program Early CT Score 0–2 (OR, 1.45 [95% CI, 1.17–1.80]) when compared with MM alone.ConclusionOur results confirm the efficacy of EVT for acute ischemic stroke with large core and suggest a consistent benefit across all Alberta Stroke Program Early CT Score categories. These results represent an important shift in the current large vessel occlusion selection paradigm that currently considers core as an effect modifier for EVT selection.